Mengelola Kualitas dalam Perusahaan Jasa - Prihatno (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2010)
In a Higly Competitive era, every company must give full attention to quality, becouse qualityhas a elose relationship with customer satisfaction and quality proviels an incentives to customer to establish strong ties with the company. In the long trem the company needs of understand the expectation and needs of customers to improve customer satisfaction, which the company shouldbe able to maximize the customer experience the fun and minimize the customer experience. One approach that can be used is to approach the quality of service that bluids on two mayor factor is customer perceotion of service received by actual service ecpected measurement of quality of service as very important for company, becouse it is useful to measure the gap between customer expectation and perception about the service provided by the company. Quality management frame work is considered important especially to assess and manage the quality of service.